Studi Persepsi Petambak Tradisional Terhadap Pelestarian Hutan Mangrove Di Desa Tanjung Limau Kecamatan Muara Badak Kabupaten Kutai Kartanegara - Ani Astuti; Bambang Indratno Gunawan; Qoriah Saleha (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
This study aimed to find out the traditional fish farmers’ perception of mangrove forest conservation in Tanjung Limau Village, Muara Badak Sub-district, Kutai Kartanegara Regency. The method of this study was purposive sampling based on the number of traditional fish farmers who were still productive in brackishwater pond cultivation, namely 15 respondents. The method of data analysis was descriptive statistical analysis. The data for scores (the highest was 5 and the lowest was 1) from the questionnaire were based on the Likert Scale. The result showed that the cumulative score for the respondents’ perception of the 7 criteria for mangrove forest management was 125.33 in the range score between 105.43–130.23 categorized as Agree. It is a positive point from the traditional fish farmers since they agree with making the mangrove forest stay conserved. The mangrove forest conservation is not only the people’s responsibility but is also a shared responsibility to make the mangrove forest sustainable.